2007
DOI: 10.1074/jbc.c600319200
|View full text |Cite
|
Sign up to set email alerts
|

Janus Kinase 3 Regulates Interleukin 2-induced Mucosal Wound Repair through Tyrosine Phosphorylation of Villin

Abstract: Janus kinase 3 (Jak3) is a non-receptor tyrosine kinase known to be expressed in hematopoietic cells. Studies of whole organ homogenates show that Jak3 is also expressed in the intestines of both human and mice. However, neither its expression nor its function has been defined in intestinal epithelial enterocytes. The present studies demonstrate that functional Jak3 is expressed in human intestinal enterocytes HT-29 Cl-19A and Caco-2 and plays an essential role in the intestinal epithelial wound repair process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 23 publications
(31 reference statements)
5
79
0
Order By: Relevance
“…2A, Jak3-V484* was tyrosine-phosphorylated both in vitro using the TKX1 expression system (first and second panels) and in stably transfected mammalian cells (HT-29Cl-19A) upon IL-2 activation (third and fourth panels). Previously, we showed that IL-2 treatment led to tyrosine phosphorylation of Jak3 in HT-29cl19A cells that facilitated its interactions with villin that enhanced IL-2-induced wound repair (8). Here we showed that IL-2 treatment also led to tyrosine phosphorylation of Jak3-V484* that co-immunoprecipitated with villin only in the presence of IL-2 (Fig.…”
Section: Recombinant Jak3 Autophosphorylates Itself and Transphosphormentioning
confidence: 62%
See 4 more Smart Citations
“…2A, Jak3-V484* was tyrosine-phosphorylated both in vitro using the TKX1 expression system (first and second panels) and in stably transfected mammalian cells (HT-29Cl-19A) upon IL-2 activation (third and fourth panels). Previously, we showed that IL-2 treatment led to tyrosine phosphorylation of Jak3 in HT-29cl19A cells that facilitated its interactions with villin that enhanced IL-2-induced wound repair (8). Here we showed that IL-2 treatment also led to tyrosine phosphorylation of Jak3-V484* that co-immunoprecipitated with villin only in the presence of IL-2 (Fig.…”
Section: Recombinant Jak3 Autophosphorylates Itself and Transphosphormentioning
confidence: 62%
“…1A) was done using pY20 (the top panel) and anti-GST (second from the top) antibodies. Tyrosine phosphorylation of Jak3-V484* in human IEC was determined by stable transfection of pCDNA-HA-Jak3-V484* into HT-29 Cl-19A cells treated with or without 50 units/ml of IL-2 for 15 min as reported before (8). Equal amounts of proteins from the cell lysates were subjected to IP using anti-HA antibody followed by IB using either pY20 (third from the top) or anti-HA (fourth from the top) antibody.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations